Baseline disability in activities of daily living predicts dementia risk even after controlling for baseline global cognitive ability and depressive symptoms. (12th September 2012) - Fauth, Elizabeth B.; Schwartz, Sarah; Tschanz, JoAnn T.; Østbye, Truls; Corcoran, Christopher; Norton, Maria C.
<x xml:space="preserve">Abstract</x> Objectives Late‐life disability in activities of daily living (ADL) is theorized to be driven by underlying cognitive and/or physical impairment, interacting with psychological and environmental factors. Although we expect that cognitive deficits would explain associations between ADL disability and dementia risk, the current study examined ADL as a predictor of future dementia after controlling for global cognitive status. Methods The population‐based Cache County Memory Study (N = 3547) assessed individuals in four triennial waves (average age 74.9 years, years of education 13.36 years; 57.9% were women). Cox proportional hazards regression models assessed whether baseline ADL disability (presence of 2+ Instrumental ADL and/or 1+ Personal ADL) predicted incident dementia after controlling for APOE status, gender, age, baseline cognitive ability (Modified Mini‐mental State Exam, 3MS‐R; adjusted for education level), and baseline depressive symptoms (Diagnostic Interview Schedule). Results Over the course of study, 571 cases of incident dementia were identified through in‐depth cognitive assessment, ending in expert consensus diagnosis. Results from Cox models suggest that ADL disability is a statistically significant predictor of incident dementia (adjusted hazard ratio = 1.83, p < 0.001), even after controlling for covariates. Conclusions Findings suggest that ADL disability offers unique contributions in risk for incident dementia, even after controlling for global cognitive status. We discuss how physical impairment and executive function may play important roles in this relationship, and how ADL is useful, not just a diagnostic tool at, or after dementia onset, but also as a risk factor for future dementia, even in individuals not impaired on global cognitive tests. Copyright © 2012 John Wiley & Sons, Ltd.